Subclasses of Temporal and Spatial Phrases in Portuguese – Location vs. Mere Reference - Móia, Telmo (2018)
This paper deals with the diversity of temporal and spatial phrases – mainly those headed by prepositions or preposition-like connectives – that convey locating information or involve mere temporal/spatial reference. It shows that the different subclasses are quite heterogeneous in Portuguese, and exhibit interesting, syntactically complex, patterns. A certain degree of instability in their use, likely indicative of linguistic change (mainly in Standard European Portuguese), is illustrated through the use of corpora examples. English data is often used for comparison. The formal framework underlying the linguistic analyses is Discourse Representation Theory (cf. Kamp & Reyle 1993).